Preparation of antimony tin oxide water-based antibacterial colloid and application of antimony tin oxide water-based antibacterial colloid in heat-insulating glass coating
By grafting or covering small molecules and dispersants on the surface of antimony oxide particles, the modified antimony oxide material significantly improves the dispersion and thermal insulation performance in the thermal insulation coating, solving the existing materials in thermal insulation coating The problem of poor agglomeration and dispersion performance in the process achieves a balance between infrared shielding and visible light transmittance.
Patent Information
- Application Number
- CN202411350888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-28
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The existing antimony-oxide tin materials are prone to agglomeration in the thermal insulation coating, have poor dispersion performance, and it is difficult to achieve good infrared shielding and visible light transmittance balance in transparent thermal insulation glass coating.
By grafting or covering small molecules and dispersants on the surface of antimony oxide particles, ultrasonic and sand dispersion technology are used to improve their dispersion performance, forming modified antimony oxide hydrocarbons, and enhancing their compatibility with polymer matrix and thermal insulation properties.
It achieves good dispersion of antimony oxide tin material, significantly improves thermal insulation performance and transparency, reduces the amount of addition, and has environmentally friendly processes and low cost, making it suitable for industrial production.
Smart Images

Figure HDA0005062329340000011 
Figure HDA0005062329340000012 
Figure HDA0005062329340000021
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano material antibacterial colloids, and in particular to application of a modified antimony tin oxide material in a glass heat insulation coating. Background Art
[0002] Thermal insulation transparent coatings have attracted more and more attention from researchers due to their demand and wide application in the fields of automotive glass, glass curtain walls, indoor window glass, etc. However, in order to make the coating transparent and heat-insulating, there needs to be a balance between the low transmittance of ultraviolet and infrared rays and the high transmittance of most visible light, which is the focus that researchers need to consider most. Therefore, the application of nanomaterials in the absorption and shielding of ultraviolet and infrared rays and high visible light transmittance is the focus of current research.
[0003] Transparent heat-insulating glass coating mainly prepares a transparent coating with heat-insulating properties by evenly dispersing nano-fraction materials with heat-insulating functions in a solvent and blending them with functional transparent resins. Generally speaking, the coating can have an infrared shielding rate of 80-90% and at the same time ensure a visible light transmittance of 65-70%. This requires that the powder material with heat-insulating functions has good dispersion properties and no large particle agglomeration occurs in the coating matrix.
[0004] The invention uses antimony tin oxide split, a mature product on the market, which is ground and dispersed, and uses technical means of small molecule grafting and dispersant coating to effectively graft or coat small molecules and dispersants on the surface of antimony tin oxide dispersed particles, thereby improving the dispersion performance thereof, and overcoming the phenomenon that the antimony tin oxide material tends to be stable and form agglomerations due to the thermodynamic and kinetic instability of particles after dispersion. The invention has the advantages of good antimony tin oxide dispersion performance, simple technology, low production cost, good heat insulation performance, environmentally friendly production process, non-toxic raw materials and very easy mass production. Summary of the invention
[0005] Based on this, the present invention provides a modified antimony tin oxide material, which solves the problems of easy agglomeration and poor dispersion performance, and enhances its application in the field of thermal insulation coatings. It has the advantages of small addition amount, good thermal insulation performance, good coating transparency, etc.
[0006] The present invention is achieved through the following technical solutions.
[0007] A modified antimony tin oxide, the modified antimony tin oxide material comprising: antimony tin oxide coated or grafted with small molecules on the surface;
[0008] In one embodiment, the small molecule is one or more of sodium polyacrylate, sodium hexametaphosphate, sodium methylene bisnaphthalene sulfonate and polyethylene glycol.
[0009] In one of the embodiments, the mass ratio of the small molecule to the antimony tin oxide is (0.05-0.1):1.
[0010] The present invention also provides a water-based heat-insulating glass coating having excellent heat-insulating performance prepared by using the modified antimony tin oxide colloid as described above in the water-based glass coating.
[0011] The present invention also provides a method for preparing the modified antimony tin oxide aqueous colloid as described above, comprising the following steps:
[0012] The antimony tin oxide, one or more of the small molecules are uniformly mixed with a dispersion medium, and ultrasonic dispersion, sand milling dispersion and other technical means are used.
[0013] In one embodiment, the grinding method adopts a sand mill dispersion method.
[0014] In one embodiment, the grinding media used in the sand milling dispersion is zirconium oxide beads.
[0015] In one embodiment, the particle size of the zirconia beads is 0.1 mm to 0.3 mm.
[0016] In one embodiment, the sanding conditions include: a rotation speed of 2000 r / min to 3000 r / min; and a duration of 1 h to 8 h.
[0017] In one of the embodiments, the mass ratio of the small molecule, the antimony tin oxide and the dispersion medium is (0.05-0.1):1:(5-100).
[0018] In one embodiment, the dispersion medium is laboratory-prepared pure water.
[0019] Compared with the prior art, the modified antimony tin oxide colloid of the present invention has the following beneficial effects:
[0020] The invention coats or grafts small molecules or dispersants onto the surface of antimony tin oxide particles, so that the antimony tin oxide particles and the modified small molecules are grafted to form a certain steric hindrance, and the addition of the dispersant enhances the electrostatic repulsion between the particles, reduces the influence of hydrogen bonds, van der Waals forces and hydrogen bonds between the particles, and prepares an antimony tin oxide aqueous colloidal solution with good dispersion, overcomes the secondary agglomeration phenomenon of antimony tin oxide, and visually sees a clear and transparent modified antimony tin oxide aqueous colloidal material with good Tyndall effect and preservation performance. The particle size is less than 100 nm after dynamic light scattering detection, thereby realizing the excellent performance display of the antimony tin oxide itself. Compared with the original antimony tin oxide split material, the modified antimony tin oxide aqueous colloidal solution has better dispersion performance, better compatibility with a polymer matrix, better heat insulation performance, lower addition amount and better coating transparency performance.
[0021] Furthermore, the modified antimony tin oxide material of the present invention has safe and environmentally friendly raw materials, simple production process, simple operation, and can be easily scaled up for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The product diagram provided by the present invention; wherein, the left side is the antimony tin oxide aqueous solution after ultrasonic modification, which is the physical diagram of comparative example 1, the middle side is the antimony tin oxide aqueous solution after ultrasonic modification with small molecules, which is the physical diagram of comparative example 2, and the right side is the antimony tin oxide aqueous colloidal solution after sand milling with small molecules, which is the physical diagram of embodiment 6;
[0023] Figure 2 This is a particle size test graph (DLS) of Example 6 of the modified antimony tin oxide provided by the present invention;
[0024] Figure 3 The present invention provides a tin-Tyndall effect test of the modified antimony oxide; wherein the left side is a physical picture of comparative example 1, the middle is a physical picture of comparative example 2, and the right side is a physical picture of embodiment 6.
[0025] Figure 4 The present invention provides a physical picture of Example 6 of the glass coating with antimony tin oxide added after drying.
[0026] Figure 5 The present invention provides a test of the heat insulation performance of the glass coating added with antimony tin oxide after drying. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0028] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0029] The words "preferably", "more preferably" and the like in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0030] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0032] The present invention provides a modified antimony tin oxide material, which comprises: antimony tin oxide with small molecules grafted or coated on the surface;
[0033] Among them, the small molecules are sodium polyacrylate, sodium hexametaphosphate, sodium methylene bisnaphthalene sulfonate and polyethylene glycol.
[0034] These small molecules can be used as food-grade additives due to their different molecular weights and preparation processes.
[0035] In a specific example, the antimony tin oxide is commercially available antimony tin oxide.
[0036] In a specific example, the particle size of antimony tin oxide is 2000 nm to 14000 nm.
[0037] In a preferred example, the antimony tin oxide has a purity of 99.9%.
[0038] In a preferred example, the small molecule is selected from sodium polyacrylate (food grade), sodium hexametaphosphate (food grade), sodium methylene bisnaphthalene sulfonate (analytical grade) and polyethylene glycol-2000.
[0039] In a specific example, all small molecules can be used as food additives.
[0040] In a specific example, the small molecule is selected from polyethylene glycol-2000.
[0041] In a specific example, the average particle size of the antimony tin oxide with small molecules grafted or coated on the surface is less than 100 nm. Preferably, the particle size of the antimony tin oxide with small molecules grafted or coated on the surface is 72 nm.
[0042] In a specific example, the mass ratio of the total mass of small molecules to antimony tin oxide is (0.05-0.1):1.
[0043] The present invention also provides a method for using the modified antimony tin oxide aqueous colloidal material in a glass coating to prepare a heat-insulating transparent glass coating.
[0044] The present invention also provides a method for preparing the modified antimony tin oxide aqueous colloidal material, comprising the following steps:
[0045] Mix antimony tin oxide, small molecules and dispersion medium evenly, and pour into the material barrel of the sand mill after ultrasonic treatment.
[0046] In a specific example, the grinding method is sand mill dispersion.
[0047] In one specific example, the grinding media of the sand mill is zirconium oxide beads.
[0048] In a specific example, the particle size of the zirconia beads is 0.1 mm to 0.3 mm.
[0049] It can be understood that the particle size of the zirconia beads includes but is not limited to 0.1 mm, 0.20 mm, 0.30 mm, etc. In a preferred example, the particle size of the zirconia beads is 0.2 mm.
[0050] In a specific example, the sanding conditions include: the rotation speed of the sanding agent is 2000 r / min to 3000 r / min.
[0051] In a specific example, the conditions for sand grinding and dispersion include: the sand grinding time is 1 hour to 8 hours.
[0052] In a specific example, the mass ratio of the total mass of small molecules to antimony tin oxide is (0.05-0.1):1.
[0053] In a specific example, the mass ratio of antimony tin oxide to the dispersion medium is 1:(5-100).
[0054] In a specific example, the dispersion medium is water. More specifically, the pH of water is 7.0. The pH of the reaction system is set to 7.0-8.6, which will not cause major pollution to the environment.
[0055] In a preferred example, the water is laboratory-prepared purified water.
[0056] In a preferred example, the mechanical-chemical modification is carried out in a sand mill at room temperature and pressure. During the sand milling process, the collision of the grinding medium will increase the temperature in the sand mill chamber and the temperature of the grinding slurry. The sand milling experiment uses a water chiller and a heat exchanger to cool the circulating grinding antimony tin oxide slurry.
[0057] In a preferred example, a sand mill is used to conduct a small test. After the antimony tin oxide is sand-milled to the nanometer level, "reactive sites" are formed on the surface of the antimony tin oxide particles, which are grafted with polyethylene glycol small molecules or coated with dispersants on the dispersed antimony tin oxide surface, forming steric hindrance between the antimony tin oxide particles, reducing the effects of van der Waals forces and hydrogen bonds between particles, and increasing the electrostatic repulsion between particles, effectively overcoming the phenomenon that antimony tin oxide tends to agglomerate due to the kinetic and thermodynamic instability caused by the smaller particle size and the larger specific surface area.
[0058] In a more specific example, the preparation method of the modified antimony tin oxide material comprises the following steps:
[0059] Zirconia beads with a particle size of 0.1mm to 0.3mm are added to the chamber of the sand mill, and then small molecules or dispersants, antimony tin oxide powder and water with a mass ratio of (0.05 to 0.1):1:(5 to 100) are weighed and placed in a beaker. After stirring and dispersing, they are poured into the material barrel of the sand mill after ultrasonication and the sand mill is turned on. The sand milling speed is set to 2000r / min to 3000r / min, and the sand milling time is set to 1h to 8h. After the experiment is completed, the feed liquid in the sand mill is transferred to the material barrel, the sand mill speed is turned off, and the dispersed modified antimony tin oxide aqueous colloidal solution in the feed liquid tank is extracted.
[0060] The modified antimony tin oxide material and its preparation method of the present invention are further described in detail below in conjunction with specific examples. The raw materials used in the following examples are all commercially available products unless otherwise specified. The antimony tin oxide used has a purity of 99.9% and is a commercially available antimony tin oxide powder. The small molecules used are food additives, and the dispersion medium used is laboratory-made purified water.
[0061] Example 1
[0062] This embodiment provides a method for preparing a modified antimony tin oxide aqueous colloidal material, which is as follows:
[0063] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber. Weigh 2 g of commercially available antimony tin oxide powder and 0.08 g of low-molecule polyethylene glycol-2000, pour them into a 3 L beaker, add 2 kg of pure water to the beaker, stir and disperse, pour into the sand mill material barrel after ultrasonic treatment, set the sand mill speed to 2500 r / min, and set the sand mill time to 6 h.
[0064] Step 2: After the sand milling is completed, the prepared aqueous slurry is pumped into a material barrel, and the polyethylene glycol-grafted antimony tin oxide colloidal solution is released.
[0065] Step 3: The particle size of the antimony tin oxide colloidal solution grafted with polyethylene glycol is tested using a Malvern Zeta Potential-Lab.
[0066] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0067] Example 2
[0068] This embodiment provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0069] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber. Weigh 2 g of commercially available antimony tin oxide powder and 0.08 g of dispersant sodium hexametaphosphate, pour them into a 3 L beaker, add 2 kg of pure water to the beaker, stir and disperse, pour into the sand mill material barrel after ultrasonic treatment, set the sand mill speed to 2500 r / min, and set the sand mill time to 6 h.
[0070] Step 2: After the sand milling is completed, the prepared aqueous slurry is pumped into a material barrel to release the antimony tin oxide colloidal solution coated with sodium hexametaphosphate.
[0071] Step 3: The antimony tin oxide colloidal solution coated with sodium hexametaphosphate is tested for particle size using a Malvern Zeta Potential-Lab test device.
[0072] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0073] Example 3
[0074] This embodiment provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0075] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber. Weigh 2 g of commercially available antimony tin oxide powder and 0.08 g of dispersant sodium polyacrylate, pour them into a 3 L beaker, add 2 kg of pure water to the beaker, stir and disperse, pour into the sand mill material barrel after ultrasonic treatment, set the sand mill speed to 2500 r / min, and set the sand mill time to 6 h.
[0076] Step 2: After the sand grinding is completed, the prepared aqueous slurry is pumped into a material barrel, and the antimony tin oxide colloidal solution coated with sodium polyacrylate is released.
[0077] Step 3: The antimony tin oxide colloidal solution coated with sodium polyacrylate is subjected to particle size detection using a Malvern Zeta Potential-Lab.
[0078] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0079] Example 4
[0080] This embodiment provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0081] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber. Weigh 2 g of commercially available antimony tin oxide powder and 0.08 g of dispersant sodium methylene bisnaphthalene sulfonate, pour them into a 3 L beaker, add 2 kg of pure water to the beaker, stir and disperse, pour into the sand mill material barrel after ultrasonic treatment, set the sand mill speed to 2500 r / min, and set the sand mill time to 6 h.
[0082] Step 2: After the sand milling is completed, the prepared aqueous slurry is pumped into a material barrel to release the antimony tin oxide colloidal solution coated with sodium methylene bisnaphthalene sulfonate.
[0083] Step 3: The antimony tin oxide colloidal solution coated with sodium methylene bisnaphthalene sulfonate is subjected to particle size detection using a Malvern Zeta Potential-Lab detection device.
[0084] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0085] Example 5
[0086] This embodiment provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0087] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber; weigh 600 g of commercially available antimony tin oxide powder, 5 g of small molecule polyethylene glycol, and 2 g of dispersant sodium methylene bisnaphthalene sulfonate, pour them into a 3 L beaker, add 2 kg of pure water to the beaker, stir and disperse, pour into the sand mill material barrel after ultrasonication, set the sand mill speed to 2500 r / min, and set the sand mill time to 6 h.
[0088] Step 2: After the sand grinding is completed, the prepared aqueous slurry is pumped into a material barrel, and the coated grafted antimony tin oxide colloidal solution is released.
[0089] Step 3: The particle size of the coated and grafted antimony tin oxide colloidal solution is tested using a Malvern Zeta Potential-Lab.
[0090] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0091] Example 6
[0092] This embodiment provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0093] Step 1: Weigh about 1.5 kg of zirconia beads with a particle size of 0.2 mm and add them to a 0.3 L sand mill chamber; weigh 600 g of commercially available antimony tin oxide powder, 6 g of small molecule polyethylene glycol, 3 g of dispersant sodium methylene bisnaphthalene sulfonate, 2 g of sodium polyacrylate, and 4 g of sodium hexametaphosphate; pour them into a 3 L beaker; add 2 kg of pure water to the beaker, stir and disperse, and pour them into the sand mill material barrel after ultrasonic treatment; set the sand mill speed to 3000 r / min and the sand milling time to 5 h.
[0094] Step 2: After the sand grinding is completed, the prepared aqueous slurry is pumped into a material barrel, and the coated grafted antimony tin oxide colloidal solution is released.
[0095] Step 3: The particle size of the coated and grafted antimony tin oxide colloidal solution is tested using a Malvern Zeta Potential-Lab.
[0096] Step 4: The prepared antimony tin oxide aqueous colloidal solution is subjected to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0099] Step 1: Weigh 0.5 g of antimony tin oxide powder, add it to 500 g of a laboratory-made pure water solution, stir, and set the ultrasonic time to 6 hours.
[0100] Step 2: The particle size of the antimony tin oxide colloidal solution after ultrasound is tested using a Malvern Zeta Potential-Lab.
[0101] Step three, subjecting the prepared antimony tin oxide aqueous colloidal solution to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0102] Comparative Example 2
[0103] This comparative example provides a method for preparing a modified antimony tin oxide material, which is as follows:
[0104] Step 1, weigh 600g of commercially available antimony tin oxide powder, 6g of small molecule polyethylene glycol, 3g of dispersant sodium methylene bisnaphthalene sulfonate, 2g of sodium polyacrylate, and 4g of sodium hexametaphosphate, pour them into a 3L beaker, add 2kg of pure water to the beaker, stir and disperse, and ultrasonically disperse, and the ultrasonic time is set to 4h.
[0105] Step 2: The particle size of the antimony tin oxide colloidal solution after ultrasound is tested using a Malvern Zeta Potential-Lab.
[0106] Step three, subjecting the prepared antimony tin oxide aqueous colloidal solution to a Tyndall effect test, wherein the test is performed by irradiating the solution with a laser pen.
[0107] The present invention provides a method for preparing a transparent heat-insulating ratio of a modified antimony tin oxide material, which is specifically as follows:
[0108] Step 1, weigh 10g of each of the aqueous antimony tin oxide slurries prepared in Example 6, Comparative Example 1 and Comparative Example 3, and introduce them into a beaker containing 50g of glass coating (the glass coating is homemade in the laboratory and is currently sold on the market), stir, set the stirring time to 10min, set the stirring speed to 350r / min, filter, spray on the glass substrate, and dry, set the drying temperature to 50°C, and set the drying time to 6min.
[0109] Step 2: Test the light transmittance of the dried transparent glass by visual inspection.
[0110] Step three, testing the transmittance of the prepared glass coating under ultraviolet light, infrared light, and visible light.
[0111] Step three, testing the heating performance of the prepared glass coating under light irradiation.
[0112] Figure 1On the left is the product of ultrasonic dispersion of antimony tin oxide in aqueous emulsion, in the middle is the solution of small molecules grafted or coated on the surface of antimony tin oxide after stirring and ultrasonication, and on the right is the antimony tin oxide aqueous colloidal solution prepared by stirring, ultrasonic dispersion and sand milling. Figure 1 The comparison shows that at the same mass concentration, antimony tin oxide has poor dispersion performance after ultrasound without adding any small molecules and dispersants. The color of the solution is the initial color of antimony tin oxide, and the particle size is about 500nm. After adding small molecules and dispersants and ultrasonic dispersion, antimony tin oxide has certain dispersion performance, and the color of the solution also turns brown. The particle size at this time is about 100nm. It may be due to the smaller particle size and the color development effect of the nanomaterial absorbing different wavelengths of light in optical properties. After adding small molecules and dispersants, stirring and ultrasonic dispersion, the antimony tin oxide aqueous solution after grinding and dispersion in a sand mill is a colloid with a clear and transparent effect. Its particle size is tested to be 72nm.
[0113] Figure 2 The Tyndall effect test of the emulsion of antimony tin oxide in aqueous solution without adding small molecules and dispersants in ultrasonic dispersion, the Tyndall effect test of the antimony tin oxide aqueous solution after ultrasonic dispersion with the same small molecules and dispersants, and the Tyndall effect test of the antimony tin oxide aqueous colloidal solution after stirring, ultrasonic dispersion and sand mill dispersion. The results show that antimony tin oxide without adding small molecules and dispersants is difficult to disperse in aqueous media, and some powders sink to the bottom. After ultrasonic dispersion of small molecules and dispersants, the dispersibility of antimony tin oxide becomes better, and a nano-optical effect caused by a smaller particle size appears, and the solution appears brown. After stirring, ultrasonic dispersion and sand mill dispersion modification, antimony tin oxide has a good dispersing effect. After sand mill dispersion breaks up the antimony tin oxide particles and makes them smaller, the small antimony tin oxide particles are dispersed under the high energy of sand mill. , "active sites" for reaction grafting are formed on the surface of small particles, so that small molecules can be well grafted on the surface of small antimony tin oxide particles. At the same time, the dispersant is coated on the surface of small particles, which is conducive to the formation of steric hindrance between dispersed particles. After the dispersant is coated on the surface of small particles, the electrostatic attraction between particles can be changed into electrostatic repulsion, reducing the effect of van der Waals force and hydrogen bond between particles, so that stable dispersed small particles are formed between particles and are evenly dispersed in water to form aqueous colloids. It can be seen from the figure that the antimony tin oxide solution after ultrasonic treatment and the antimony tin oxide solution after ultrasonic treatment with small molecules added do not have obvious Tyndall effect, while the antimony tin oxide aqueous colloid solution after sand milling modification has obvious Tyndall effect, and the small antimony tin oxide particles cannot be centrifuged out by high-speed centrifugation at 12000r / min in a centrifuge.
[0114] The heat-insulating coating prepared from the solution obtained in Examples 1 to 6 and Comparative Examples 1 and 6 is sprayed on a glass substrate after being blended, stirred, filtered, and then sprayed. Several representative pictures are mainly selected. Figure 3 It can be seen that there is no significant change in the transmittance of the ordinary glass and the glass sprayed with the glass coating and the glass with 20% of the sample of Example 6 added. Due to the color of the antimony tin oxide material itself, the glass coating after spraying 20% of Example 6 will have some blue changes, while Figure 4 It shows that after 20% of the glass coatings of Comparative Example 1 and Comparative Example 2 are sprayed on the glass surface, the surface becomes blurred and the light transmittance is deteriorated.
[0115] Table 1 shows the transparent heat-insulating coating prepared by blending the prepared nano heat-insulating slurry with the glass coating matrix in Example 6 and Comparative Examples 1-2, and the ultraviolet light, infrared light, visible light transmittance test and transparency test are performed on the coating, the transparency test is visual inspection, and the test results of the temperature rise performance under light irradiation. It can be seen from the table that the visible light transmittance of Comparative Example 6 with 20% of the comparative example added is 82.4%, the infrared shielding rate is 88.6%, and the ultraviolet shielding rate is 98.8%, while after adding the same mass of Comparative Example 1 and Comparative Example 2, the infrared shielding rate of the coating is reduced, and the visible light transmittance is also reduced, especially the surface of Comparative Example 1 with 20% added is basically blurred, the visible light transmittance is only 52.3%, and the ultraviolet shielding rate is only 57.6%.
[0116] Combination Figure 5 It can be seen from the test results that, under the same irradiation time, the temperature of the glass without Example 6 rises to 88.2°C, while the temperature of the glass with 20% of Example 6 rises to 114°C, and the temperature difference is 25.8°C, which means that the antimony tin oxide prepared by the present invention has a good infrared shielding rate and excellent thermal insulation performance.
[0117] Sample No. VLT(550nm) IRR(1400nm) UVR(365nm) Example 6 82.4% 88.6% 98.6% Comparative Example 1 52.3% 32.6% 78.5% Comparative Example 2 72.4% 75.2% 95.2%
[0118] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0119] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to interpret the contents of the claims.
Claims
1. A modified antimony tin oxide aqueous colloidal material, characterized in that: The modified antimony tin oxide material comprises: antimony tin oxide with small molecules grafted or coated on the surface; Wherein, the small molecule is one or more of sodium hexametaphosphate, polyethylene glycol, sodium methylene bisnaphthalene sulfonate, and sodium polyacrylate.
2. The modified antimony tin oxide material according to claim 1, characterized in that: The above mentioned substances are sodium hexametaphosphate (analytical grade), polyvinyl alcohol-2000, sodium polyacrylate (food grade), and sodium methylene bisnaphthalene sulfonate (analytical grade).
3. The modified antimony tin oxide material according to claim 1, characterized in that: The small molecule or dispersant is one or more of them.
4. The modified antimony tin oxide material according to claim 1, characterized in that: The mass ratio of the small molecule or dispersant to the antimony tin oxide is (0.05-0.1):
1.
5. Use of the modified antimony tin oxide material according to any one of claims 1 to 4 in preparing heat insulation in glass coatings.
6. A method for preparing the modified antimony tin oxide material according to any one of claims 1 to 4, characterized in that: The steps include: The antimony tin oxide, the small molecule or the dispersant and the dispersion medium are mixed by ultrasonication and ground.
7. The method for preparing the modified antimony tin oxide material according to claim 6, characterized in that: The grinding method is sand grinding dispersion.
8. The method for preparing the modified antimony tin oxide material according to claim 7, characterized in that: The grinding media used in sand milling dispersion is zirconium oxide beads.
9. The method for preparing modified antimony tin oxide according to claim 8, characterized in that: The particle size of the grinding medium zirconium oxide beads is 0.1 mm to 0.3 mm.
10. The method for preparing the modified antimony tin oxide material according to claim 7, characterized in that: The conditions for sand grinding include: a rotation speed of 2000 r / min to 3000 r / min; a duration of 1 h to 8 h.
11. The method for preparing the modified antimony tin oxide material according to claim 6, characterized in that: One or more of the small molecules or dispersants, the mass ratio of the antimony tin oxide to the dispersion medium is (1-50):(100-1000).
12. The method for preparing the dispersed modified antimony tin oxide material according to any one of claims 6 to 11, characterized in that: The dispersion medium is pure water.